Enhancing Neoplasm Expression in Field Pea (Pisum sativum) via Intercropping and Its Significance to Pea Weevil (Bruchus pisorum) Management - Teshome, Abel; Bryngelsson, Tomas; Mendesil, Esayas; Marttila, Salla; Geleta, Mulatu (Frontiers in Plant Science, 2016)
Neoplasm formation, a non-meristematic tissue growth on young field pea (Pisum sativum L.) pods is triggered in the absence of UV light and/or in response to oviposition by pea weevil (Bruchus pisorum L.). This trait is expressed in some genotypes (Np genotypes) of P. sativum and has the capacity to obstruct pea weevil larval entry into developing seeds. In the present study, 26% of the tested accessions depicted the trait when grown under greenhouse conditions. However, UV light inhibits full expression of this trait and subsequently it is inconspicuous at the field level. In order to investigate UV light impact on the expression of neoplasm, particular Np genotypes were subjected to UV lamp light exposure in the greenhouse and sunlight at the field level. Under these different growing conditions, the highest mean percentage of neoplastic pods was in the control chamber in the greenhouse (36%) whereas in single and double UV lamp chambers, the percentage dropped to 10% and 15%, respectively. Furthermore, when the same Np genotypes were grown in the field, the percentage of neoplastic pods dropped significantly (7%). In order to enhance neoplastic expression at the field level, intercropping of Np genotypes with sorghum was investigated. As result, the percentage of neoplastic pods was threefold in intercropped Np genotypes as compared to those without intercropping. Therefore, intercropping neoplastic genotypes with other crops such as sorghum and maize can facilitate neoplasm formation, which in turn can minimize the success rate of pea weevil larvae entry into developing seeds. Greenhouse artificial infestation experiments showed that pea weevil damage in neoplastic genotypes is lower in comparison to wild type genotypes. Therefore, promoting neoplastic formation under field conditions via intercropping can serve as part of an integrated pea weevil management strategy especially for small scale farming systems.